2017
DOI: 10.1007/s00213-017-4601-1
|View full text |Cite
|
Sign up to set email alerts
|

Individual prolactin reactivity modulates response of nucleus accumbens to erotic stimuli during acute cannabis intoxication: an fMRI pilot study

Abstract: Cannabis intoxication increases activation of the right nucleus accumbens to erotic stimuli. This effect is limited to users whose prolactin is not elevated in response to intoxication. This effect may be useful in the treatment of low sexual desire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…43 A recent investigation by Androvicova et al validated these results by showing that cannabis intoxication increased activation of the right nucleus accumbens upon presentation of erotic stimuli, leading the authors to conclude that cannabis may help in the treatment of hypoactive sexual desire. 44 In contrast to these findings, animal studies demonstrated reduced libido after acute and chronic cannabis administration. Using 5 mg/kg THC Murphy et al found that 30 minutes after THC injection the percent of male rats showing copulatory behavior with sexually receptive females was significantly diminished.…”
Section: Sexual Functionmentioning
confidence: 96%
“…43 A recent investigation by Androvicova et al validated these results by showing that cannabis intoxication increased activation of the right nucleus accumbens upon presentation of erotic stimuli, leading the authors to conclude that cannabis may help in the treatment of hypoactive sexual desire. 44 In contrast to these findings, animal studies demonstrated reduced libido after acute and chronic cannabis administration. Using 5 mg/kg THC Murphy et al found that 30 minutes after THC injection the percent of male rats showing copulatory behavior with sexually receptive females was significantly diminished.…”
Section: Sexual Functionmentioning
confidence: 96%
“…Cortisol levels were also higher after inhalation of MJ vs. unintoxicated baseline levels in an fMRI study examining the aphrodisiacal effects of MJ in MJ users. However, there were no differences in cortisol levels between MJ users with or without prior aphrodisiacal experiences, so its effect on brain activity was not examined further ( 18 ). Considering the lack of standardization of MJ administration, caution should be used when drawing conclusions based on these results.…”
Section: Effects Of Thc Administration and Acute Marijuana Use On Hpamentioning
confidence: 99%
“… 22 In humans, a study using functional magnetic resonance imaging revealed that cannabis intoxication modulates the response of the right nucleus accumbens to visual erotic stimuli. 23 The nucleus accumbens is involved in the processing of the rewarding effects of sexual behavior, and activation of dopamine receptors in this brain region is shown to increase sexual motivation even among sexually satiated rodents. 24 , 25 The cannabinoid composition of consumed cannabis may modulate the effect on sexual behavior, as well.…”
Section: Discussionmentioning
confidence: 99%